Liquid Soap with Pineapple Hump Extract and Nanoformulation Against Staphylococcus aureus - Lubis, Minda Sari; Fauzi, Ziza Putri Aisyia; Dewi, Sri Harti; Rani, Zulmai; Yuniarti, Rafita (Sciences of Pharmacy, 2025)
Staphylococcus aureus is a Gram-positive bacterium that frequently causes skin infections and can become resistant to various antibiotics. Pineapple (Ananas comosus) waste, particularly the hump, contains active compounds such as bromelain, saponins, and flavonoids with known antibacterial properties. This study aimed to determine the antibacterial potential of liquid soap formulated with extract and nanoextract of pineapple hump against S. aureus. The pineapple hump was extracted using maceration with 96% ethanol, followed by nanoparticle formulation using a high-speed homogenization method. Liquid soap was made with three formulas, one formula contains a concentration of 12.5% extract and two formulas contain 1.25% nanoextract of pineapple hump. Antibacterial activity was evaluated using the disc diffusion method, and the diameter of the inhibition zones was measured. Results showed that all tested concentrations produced antibacterial activity, with the 12.5% concentration (Formula 1) exhibiting the highest inhibition zone (23.2 mm), followed by 1.25% nanoextract nano liquid soap (18.41 mm) (Formula 3) and 1.25% nanoextract liquid soap (14.53 mm) (Formula 2). The positive control (Dettol Handwash) produced a larger inhibition zone (20.08 mm). Data analysis using one-way ANOVA revealed significant differences for each formula, with a p-value of less than 0.05. These findings indicate that nanoextract of pineapple hump formulated in liquid soap has potential as a natural antibacterial agent against S. aureus.